Building an interactive geospatial tool for post-crash emergency response time analysis - Kommineni, Namratha (My University, 2024)
This study presents the development of a data-driven geospatial tool designed to optimize emergency response strategies for vehicle crashes in Kansas. By analyzing over a decade of crash data from the Kansas Department of Transportation (KDOT) and the Fatality Analysis Reporting System (FARS), the tool provides insight into three key intervals: T1 (crash to EMS notification), T2 (EMS notification to EMS arrival), and T3 (EMS arrival to hospital). The tool emphasizes the importance of timely and efficient post-crash care, particularly in rural areas, where 36.6% of fatal crashes have response times exceeding 60 minutes, compared to only 10% in urban areas. Leveraging Python-based mapping and data analysis libraries, including OpenStreetMap and Dijkstra’s algorithm for shortest path calculations, the interactive tool allows users to visualize crash locations, EMS dispatch points, and hospital/trauma center locations. The tool helps identify high-crash regions with delayed response times and supports decision-makers in improving emergency response strategies by simulating real-time EMS routing. Through its dynamic interface, the tool offers both planning and assessment capabilities, aimed at reducing fatalities and improving emergency care, especially in rural settings. This application is particularly suited for addressing the disparity in response times between rural and urban regions and can be adapted for similar efforts in other states, supporting life-saving strategies to enhance road safety.
Keywords: Post-crash care; Emergency response; Traffic safety; Golden hour